ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENYULUH PERTANIAN LAPANGAN KECAMATAN TENGGARONG KABUPATEN KUTAI KARTANEGARA (Analysis of Factors Affecting the Performance of Agricultural Extension Worker in Tenggarong Subdistrict Kutai Kartanegara District) - DINA LESMANA; JULIANTI HAPSARI IMANINGTIAS (Universitas Mulawarman (University of Mulawarman), 2018)
This study aimed to determine the internal and external factors that affect the performance of agricultural extension worker in the Tenggarong Subdistrict of Kutai Kartanegara District. To achieve the objectives, the method used PRA, FGD, RRA, indepth interview and surveys. This study was held for 3 months (May to July 2017). Data required was primary and secondary data furthermore data analysed by descriptive and present by tabular form. The determination of catagory based on assessment or score. The result showed that internal factors that most affected the performance of agricultural extension worker was time work. External factor that most affected the performance of agricultural extension worker was incentive as extension worker. The performance showed excellent result in total score 1,091. In the future, the performance of extension worker should be improved to create significant benefit for farmers in terms of the increasing income and welfare.